(untitled) (Research, Society and Development, 2021)
The educational environment changes behavior, affective-emotional profile and influences student learning. However, the impact of this environment on health students is not known, in the context of affirmative actions and socioeconomic, demographic, cultural and quality of life variables, among themselves. Aim: to characterize the profile, compare and evaluate the perception of the educational environment by nutrition students enrolled or not by affirmative actions of a Brazilian public university. Methodology: This is a cross-sectional analytical study carried out with 141 students of the Supervised Internship in Clinical Nutrition, with 111 non-enrolled (NAA) and 30 enrolled for Affirmative Actions (AA). The students answered two questionnaires, one to characterize the socioeconomic, demographic, cultural and quality of life profile, and the other to assess the educational environment (DREEM). Results: Most participants were female, with an average age of 23 years, whites, with low per capita income and reported having stressors and emotional difficulties that interfere in the academic context. The overall DREEM score indicates a “more positive than negative” environment. Regarding the dimensions of perception of learning and social relationships, there were significant differences between AA and NAA students, in the statements “Teaching is concerned with developing my competence”; “I rarely feel alone” and “I live in a comfortable place”. Conclusion: The profile of AA students, as well as their perception of the educational environment reveal that constant interventions are necessary to bring improvements in the teaching-learning process in higher education.